BOKO HARAM OPERATIONS IN NIGERIA:THE NEXUS BETWEEN FREEDOM FIGHTERS AND TERRORISTS - Musa Abdulkarim Itodo; BINTA YAKUBU SULE (International Studies Journal)
Nigeria as a country has been plagued by extensive internal security challenges. There are spate of armed militia engagements against the federal republic of Nigeria and security agencies in the North-East Boko Haram terrorist) and armed militia and acclaimed (freedom fighters) in the South-West, South- East and South-South regions with terrible fatalities in human lives and properties. There emerged several non-state armed groups in Nigeria which began to engage in resources and identity based struggles against presumed injustice and marginality. The growing state of criminality and criminal violence from the supposed freedom fighters and terrorist made it difficult to differentiate between Boko Haram terrorist operations to the armed militia (freedom fighters). Works are abounds on terrorism and freedom fighters in Nigeria and Africa, however, a few lay emphasis on persons engaged in terrorism and freedom fighting in Nigeria and Africa are actually freedom fighters not terrorists and the nexus between Boko Haram operations and the freedom fighters in Nigeria.Indeed, this paper investigates the assertion that one man’s terrorist is another man’s freedom fighter. It also argues that because of linkages to the nature of freedom fighters, crises have been particularly useful in driving the terrorism discourse in Nigeria and Africa. But the nexus between the Boko Haram operations in Nigeria; freedom fighters and terrorisms have not been stronglyscholarly established. It is on this premise that this research paper intended to bridge the scholarly gap. That, it is important to understand the context in which they occur and the nexus between them. Linking freedom fighters or agitators toBoko Haram terrorist operations, is also an attempts to develop a conceptual discourse that explains the nexus between freedom fighters and terrorism showing how politics, resources, religion, marginalization andclimate change, perceptions are implicated in the escalating terrorism (Boko Haram in the North-East) and freedom fighting (IPOB, Niger-Delta Militants). The study traces the historiography of the nexus between terrorism and freedom fighters in Nigeria, their impacts and implications and the challenges of fighting terrorism and freedom fighters in Nigeria and Africa. Using the historical approach, primary and secondary data,and the study found that both the terrorist and freedom fighter suffer from one form of marginalization or the other prompting agitations. Social justice and equity are at the heart of thepanacea for mitigating conflicts relating toBoko Haram terrorist and freedom fightinginNigeria and Africa.